Neuropsychological Functioning and Quality of Life During the First Year after Completing Chemotherapy for Breast Cancer - Reid-Arndt, Stephanie A. (2010)
OBJECTIVE: Research has documented modest cognitive difficulties among women treated for breast cancer. The present study was designed to evaluate the effects of these subtle cognitive changes on quality of life after treatment. METHODS: Data are presented from women breast cancer patients who completed neuropsychological tests and questionnaires regarding quality of life six and twelve months post-chemotherapy (n's = 39 and 33). Neuropsychological test scores were examined for evidence of cognitive difficulties at each time point; repeated measures ANOVAs were used to identify changes over time. Regression analyses assessed relationships of quality of life outcomes with cognitive functioning, social support seeking, and fatigue. RESULTS: Small percentages of participants (< 20% across tests) evidenced deficits in delayed memory, processing speed, response inhibition, and verbal fluency at each time point. Reliable change index analyses suggested statistically reliable improvements in each cognitive domain for a modest portion of participants. Regressions revealed hesitation to seek social support and fatigue as the most consistent predictors of quality of life at six and twelve months post-chemotherapy. Cognitive complaints and verbal fluency difficulties were also significantly related to quality of life at twelve months. CONCLUSIONS: In addition to confirming the importance of fatigue and social support in quality of life, these data offer preliminary indications that weaker verbal fluency skills and self-reported cognitive complaints may be associated with poorer functional outcomes among cancer survivors. Further research is needed to validate these potential relationships, which suggest that cognitive difficulties among cancer survivors may warrant monitoring and possible intervention.